Optimization of Road Handling Priorities Using Provincial/District Roads Management System Integration and Analytical Hierarchy Process at UPT PJJ Surabaya, East Java - Nur Aini Farida; Laksono Djoko Nugroho; Haris Muhammadun (Transpublika Publisher, 2025)
This study aims to identify the priority order for road maintenance on road sections under the Surabaya Road and Bridge Management Unit (UPT PJJ Surabaya) in East Java Province by utilizing the Provincial/District Roads Management System (PKRMS) application integrated with the Analytical Hierarchy Process (AHP) method. Additionally, the study seeks to estimate the required costs for implementing the road maintenance. The research adopts a quantitative approach with a positivist philosophy. The study population consists of 123 employees from the East Java Provincial Public Works and Highways Agency, with a sample of 33 respondents selected using purposive sampling techniques. Data were collected using a mixed-method approach, involving road condition surveys conducted through the Moving Car Observer (MCO) method and a literature review. Data analysis was conducted systematically using a combination of PKRMS and AHP. The results indicate that the top-priority road section for maintenance, based on the integration of PKRMS and AHP, is the Sumberwudi–Karang Geneng section, which obtained the highest Priority Index Score (TPI) of 56. The estimated cost required for maintaining this road section is Rp16,475,545,104.98. The integration of PKRMS and AHP provides an objective, efficient, and data-driven approach, enabling local governments to optimize budgets and extend the lifespan of road infrastructure. This study recommends that local governments consistently adopt the combination of PKRMS and AHP in road infrastructure management to ensure more targeted budget allocation and enhance transparency in decision-making processes.